Albania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper explores Albania's current account (CA) deficit that improved in 2016, but remains sizable. The EBA-Lite model results indicate that the external position is moderately weaker than implied by fundamentals and desirable policy settings. Adjusting for Albania's specific circumstances, the current account gap is estimated at -1.0 percent and the real effective exchange rate is overvalued by about 6 percent, reflecting Albania's low national saving and large FDI inflows. Though Albania has benefitted from the recent tourism boom in the region, the outlook for exports remains challenging. Despite its cost competitiveness, exports are narrowly concentrated in a few low-value added sectors while new investments in the nonenergy tradable sector are limited. To close Albania's competitiveness gap and strengthen its external position, the authorities should complete key infrastructure projects to reduce transportation costs and address energy sector reliability; increase domestic savings; improve governance and the rule of law; and raise labor market efficiency by reducing skills shortages.